Perceiving patriotism China's patriotic education campaign and insights for Philippine education - Manalo, Marvie Dela Cruz (Asian Center, University of the Philippines Diliman, 2019)
"The Chinese Communist Party (CCP) implemented the Patriotic Education Campaign (PEC) in 1991 in pursuit of a new ideological tool that will serve as an agent of social integration for China in general. The Campaign not only aims to make citizens patriotic but also legitimates the one-party rule in China. While it is insightful to see how exposing more of the citizenry to artifacts of Chinese history is an effective means of cultivating patriotism (Kondo and Wu, 2011), it is also essential to witness the nuances in the Campaign as it involved various dimensions in instilling patriotism in the Chinese citizenry. It has greatly utilized schools in the implementation of the campaign among the young generations, its primary target. The CCP hopes that the PEC will instill loyalty to the Party for the continuous process of its legitimation.